Rural livelihood diversification decreases vulnerability to climate change in the Andean-Amazon foothills - Beltrán, Lucila Marcela; Cruz García, Gisella S.; Pradhan, Prajal; Quintero, Marcela (International Center for Tropical Agriculture, 2020)
A total of 256 surveys were analyzed for Caquetá and 227 surveys forYurimaguas. These surveys belong to the project "Sustainable Amazonian Landcapes" ( see below Related Datasets). All the households that participated in the survey did it freely and under prior informed consent. Households were asked about their farms’ agrobiodiversity (crops, cattle ranching, and pastoral diversity), farming activities, agroecological management practices and livelihood assets. These surveys provided the information required for defining the household typologies based on farming livelihood diversification and to obtain indicators of vulnerability to climate change. People surveyed usually were household heads or their spouses. The supervisors were the direct link with CIAT. The data was collected through Android Devices using the software CsPro 6.2 and 6.3. (Reporte Interno)